Do The Investors React to Risk Management Disclosure? (an Empirical Study on Companies in Property, Real Estate, and Building Construction Industry Listed on The Indonesia Stock Exchange Period 2016 - 2018) - Novitasari, Putri; Handayani, Rr. Sri (Universitas Muhammadiyah Surakarta, 2020)
The purpose of this research is to examine the quality of risk management according to investor reactions in property, real estate, and building construction companies listed on Bursa Efek Indonesia (BEI) in 2016-2018. The reaction of investors in this research is indicated by stock returns. In addition, this research also examines wider and more complete disclosure of the company can reduce information asymmetry with investors to make investment decisions. Based on the signaling theory, companies that disclose more information will be used as good news by investors and getting a positive reaction. The population in this research are property company, real estate company, and construction building company which registered on Bursa Efek Indonesia (BEI) in 2016 – 2018. This research is using a sampling method (purposive judgment sampling) for getting 25 from 74 company which registered on Bursa Efek Indonesia (BEI) with 75 samples. This research using multiple regression analysis.The results from the research provided that the disclosure of operations risk and empowerment risk has a positive and significant effect on stock returns while strategic risk, integrity risk, and information processing and technology risks have no significant effect on stock returns. According to this result provided that more disclosure on operations risk management and the risk of corporate empowerment can affect stock returns as a form of investor reaction, while the things that companies need to pay attention to in voluntary disclosure as additional are influence of strategic risk disclosure, integrity risk, and information processing and technology risks.